Neonatal lupus erythematosus – prevention is better than cure - Liszewska, Agata; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Neonatal lupus erythematosus (NLE) is a congenital autoimmune condition in which the transplacental passage of immunoglobulin G (IgG) directed against auto-antigens causes clinical symptoms in the foetus or neonate. Anti-Ro/SS-A, anti-La/SS-B, and to a lesser extent, anti-U1RNP autoantibodies (aAbs) have the strongest association with NLE. However, ~ 50% of affected mothers are asymptomatic despite carrying those aAbs. The clinical picture of the disease is very diverse. Cardiac manifestations are the most severe, including congenital heart block (CHB), with a mortality rate of ~18%. Preventative therapy with hydroxychloroquine (HCQ) reduces the recurrence rate of CHB in subsequent pregnancies by ~50%.